In pursuit of equity : women, men, and the quest for economic citizenship in 20th century America - Kessler-Harris, Alice (ACLS Humanities E-Book., 2001)
This volume pierces the skin of arguments and legislation to grasp the preconceptions that have shaped the experience of women: a "gendered imagination" that has defined what men and women alike think of as fair and desirable. The role of the breadwinner is investigated as a prime example.